2017
DOI: 10.1371/journal.pone.0179382
|View full text |Cite
|
Sign up to set email alerts
|

Working memory operates over the same representations as attention

Abstract: A recent study observed a working memory (WM) Stroop effect with a magnitude equivalent to that of the classic Stroop effect, indicating that WM operates over the same representations as attention. However, more research is needed to examine this proposal. One unanswered question is whether the WM Stroop effect occurs when the WM item and the perceptual task do not have an overlapping response set. We addressed this question in Experiment 1 by conducting an attentional word-color task and a WM word-color task.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
2
1
0
Order By: Relevance
“…However, another explanation is that working memory can conversely influence visual attention. Despite these apparently contradictory hypotheses, it can be concluded that there is an intimate linkage or even certain overlapping between attention and working memory (Chen, Ye, Xie, Xia, & Mo, 2017). Our data support the link between these cognitive domains due to the fact that IPV perpetrators presented both attention and working memory impairments.…”
Section: Discussionsupporting
confidence: 72%
“…However, another explanation is that working memory can conversely influence visual attention. Despite these apparently contradictory hypotheses, it can be concluded that there is an intimate linkage or even certain overlapping between attention and working memory (Chen, Ye, Xie, Xia, & Mo, 2017). Our data support the link between these cognitive domains due to the fact that IPV perpetrators presented both attention and working memory impairments.…”
Section: Discussionsupporting
confidence: 72%
“…The working memory Stroop effect is a robust and reliable congruency effect on color-naming performance, which has been well established by previous studies using the working memory Stroop task (Chen et al 2017;Kiyonaga & Egner 2014;Pan et al 2019;Wang et al 2021). However, it remains unclear what exact cognitive mechanisms drive the working memory Stroop effect.…”
Section: Introductionsupporting
confidence: 62%
“…In other words, the internal maintenance of the first number's relevant and irrelevant magnitudes in working memory per se would not reduce the size congruity effect in a numerical Stroop task, as compared to when such magnitudes are externally perceived without working memory processing (i.e., in the simultaneous presentation mode). This claim is grounded on previous research indicating that the magnitude of the Stroop effect driven by working memory maintenance is comparable to that of the classic Stroop effect (e.g., Chen et al, 2017;Kiyonaga & Egner, 2014;Pan et al, 2019). According to such studies, it would have predicted that the size congruity effect in a numerical Stroop task should be of equivalent magnitude for the sequential presentation mode (i.e., the working memory numerical Stroop task) and the simultaneous presentation mode (i.e., the classic numerical Stroop task).…”
Section: Discussionmentioning
confidence: 60%